2019
DOI: 10.1186/s12989-019-0304-6
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle exposure driven circulating bioactive peptidome causes systemic inflammation and vascular dysfunction

Abstract: Background The mechanisms driving systemic effects consequent pulmonary nanoparticle exposure remain unclear. Recent work has established the existence of an indirect process by which factors released from the lung into the circulation promote systemic inflammation and cellular dysfunction, particularly on the vasculature. However, the composition of circulating contributing factors and how they are produced remains unknown. Evidence suggests matrix protease involvement; thus, here we used a well-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
34
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 73 publications
7
34
0
1
Order By: Relevance
“…[77]. Studies have confirmed CD36 plays a critical role in vascular dysfunction caused by NP exposure [78,79]. CD36 was also reported to activate NLRP3 inflammasome in response to atmospheric particulate matter exposure [80], as well as modulating lipid accumulation in macrophage [81], ultimately contributing to the progression of atherosclerosis.…”
Section: Discussionmentioning
confidence: 93%
“…[77]. Studies have confirmed CD36 plays a critical role in vascular dysfunction caused by NP exposure [78,79]. CD36 was also reported to activate NLRP3 inflammasome in response to atmospheric particulate matter exposure [80], as well as modulating lipid accumulation in macrophage [81], ultimately contributing to the progression of atherosclerosis.…”
Section: Discussionmentioning
confidence: 93%
“…While the molecular mechanisms underlying air pollution-induced neurological outcomes are unclear, one current hypothesis is that peptide fragments shed from the lung following inhaled pollutant exposures induce mCEC dysfunction via scavenger receptors [17,34,42]. Recent studies, using the SCIP assay following pulmonary exposure to multiwalled nanomaterials, highlight extensive peptidomic changes to the serum composition that align with changes in the serum bioactivity [43]. Nanotube exposure induces elevations in circulating peptides that appear to arise from endogenous proteins, with the hypothesis that matrix metalloproteinase (MMP) activation in the lung may trigger the generation of circulating fragmented peptides.…”
Section: Introductionmentioning
confidence: 99%
“…Besides for oxLDL uptake, CD36 can also affect atherosclerosis by combining with various ligands, speci cally in regulating in ammation, endothelial dysfunction, macrophage migration, and hyperlipidemia etc [81]. Studies have con rmed CD36 plays a critical role in vascular dysfunction caused by NP exposure [82,83]. CD36 was also reported to activate NLRP3 in ammasome in response to atmospheric particulate matter exposure [84], as well as modulating lipid accumulation in macrophage [85], ultimately contributing to the progression of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%